2021
DOI: 10.1155/2021/6650097
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization Model for Tramp Ship Scheduling considering Time Window and Seaport Operation Delay Factors

Abstract: The quantity of electrical coal transported through the tramp shipping network is increasing due to the high demands. This trend has increased the scheduling difficulty combined with the underdevelopment of the private thermal power plant port. The high coal consumption and low port storage capacity requires the scheduling of the tramp ship to be on a strict time window to ensure the continuous operation of the thermal power plant. The low port unloading capacity often leads to the port congestion and delay of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Gao et al [13] described the unloading scheduling problem of a bulk cargo terminal in a large steel plant as a flexible shop scheduling problem, established a corresponding mixed-integer programming model, and proposed a column generation method to solve the optimization model. Yang et al [21] formulated a mixed-integer programming model for scheduling irregular ships in coal ports and utilized the branch pricing algorithm to optimize the scheduling of such ships. Li et al [22] formulated a multi-objective optimization model that considers multiple traffic constraints for the ship traffic scheduling problem of a shared navigation channel in the context of coal ports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gao et al [13] described the unloading scheduling problem of a bulk cargo terminal in a large steel plant as a flexible shop scheduling problem, established a corresponding mixed-integer programming model, and proposed a column generation method to solve the optimization model. Yang et al [21] formulated a mixed-integer programming model for scheduling irregular ships in coal ports and utilized the branch pricing algorithm to optimize the scheduling of such ships. Li et al [22] formulated a multi-objective optimization model that considers multiple traffic constraints for the ship traffic scheduling problem of a shared navigation channel in the context of coal ports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our second research motive is the facilitating the transport of cargo whose demand and supply are determined dynamically. Yang et al (2021) designed a tramp ship routing model to address port congestion because of static demand and supply. The result revealed that dynamic demand and supply reduce port congestion and render the system robust.…”
Section: Motivationmentioning
confidence: 99%